Motor activity and foreign language learning in preschool: A review of movement-based and total physical response interventions - Manuela Valentini; Nausicaa Simone; Alessandro Beretta (CV Rezki Media, 2026)
Background: Movement may support early foreign-language learning through embodied learning, but the preschool evidence base is fragmented. Objective: To review empirical studies on movement-based and Total Physical Response (TPR) interventions for foreign-language learning in preschool children. Method: This study employed a systematic review design based on PRISMA 2020 guidelines, involving database searches and citation tracking to identify empirical studies on movement-based and Total Physical Response (TPR) interventions in preschool foreign-language learning. Studies were screened using predefined eligibility criteria and appraised using the Mixed Methods Appraisal Tool (MMAT). Data from eligible studies were extracted and synthesized narratively due to methodological heterogeneity. Results: Eight studies met the inclusion criteria. Across stronger controlled studies, semantically integrated movement generally produced more favorable vocabulary and verbal memory outcomes than sedentary teaching or less integrated movement. Evidence focused specifically on TPR was positive in terms of engagement and short-term learning, but methodologically heterogeneous and less robust. Conclusion: Current preschool evidence supports the promise of integrated movement-based language teaching, particularly when movement is tightly aligned with instructional content. However, the evidence base remains small, largely limited to vocabulary-related outcomes, and further rigorous preschool trials are needed to clarify optimal implementation and the distinct contribution of TPR.